2022
DOI: 10.1002/anie.202214145
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Electrostatic Interaction via Strong Complexation for Highly Selective Reduction of CN into N2

Abstract: Limited by the electrostatic interaction, the oxidation reaction of cations at the anode and the reduction reaction of anions at the cathode in the electrocatalytic system nearly cannot be achieved. This study proposes a novel strategy to overcome electrostatic interaction via strong complexation, realizing the electrocatalytic reduction of cyanide (CN À ) at the cathode and then converting the generated reduction products into nitrogen (N 2 ) at the anode. Theoretical calculations and experimental results con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Furthermore, it was found that ROSs can play a significant role in the photocatalytic degradation of CIP. Moreover, other factors such as ·OH, photogenerated holes, ·O 2 – , and 1 O 2 that may cause CIP degradation were quenched by isopropyl alcohol (IPA), triethanolamine (TEOA), 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPOL), and NaN 3 , respectively. As shown in Figure c, ·OH, ·O 2 – , and 1 O 2 played major roles in the degradation reaction. It is worth noticing that when TEOA was added, the degradation efficiency was improved compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was found that ROSs can play a significant role in the photocatalytic degradation of CIP. Moreover, other factors such as ·OH, photogenerated holes, ·O 2 – , and 1 O 2 that may cause CIP degradation were quenched by isopropyl alcohol (IPA), triethanolamine (TEOA), 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPOL), and NaN 3 , respectively. As shown in Figure c, ·OH, ·O 2 – , and 1 O 2 played major roles in the degradation reaction. It is worth noticing that when TEOA was added, the degradation efficiency was improved compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…S9,† CTF-1 exhibits three peaks, which can be assigned to the C–C bonds in the benzene ring (284.7 eV), the N–CN bonds in the triazine ring (286.9 eV) and the dangling –CN group at the edge of triazine units (286.5 eV), respectively. 43,44 The new peak located at 289.1 eV, which is attributed to the carboxyl group, and the decrease in the peak area of –CN in AT-CTF-1 indicate the hydrolysis of the cyano group that generates the –COOH group (Fig. 2C and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In industry, technologies have been proposed for the harmless treatment of organic wastewater with CO 2 as the final product that was directly released into the atmosphere. However, secondary waste gas pollution, high thermodynamic stability (CO, 750 kJ mol –1 ) of CO 2 , and carbon source shortages during sewage treatment have restricted the processing and violated the carbon-neutral economy . Therefore, converting the generated flue gas from pollutant removal into value-added chemicals is a promising route to mitigate the carbon source waste and greenhouse effect.…”
Section: Introductionmentioning
confidence: 99%